Epstein–Barr Virus Acquires Its Final Envelope on Intracellular Compartments With Golgi Markers - Nanbo, Asuka; Noda, Takeshi; Ohba, Yusuke (Frontiers in Microbiology, 2018)
Herpesvirus subfamilies typically acquire their final envelope in various cytoplasmic compartments such as the trans-Golgi network (TGN), and endosomes prior to their secretion into the extracellular space. However, the sites for the final envelopment of Epstein–Barr virus (EBV), a ubiquitous human gamma herpesvirus, are poorly understood. Here we characterized the sites for the final envelopment of EBV in Burkitt’s lymphoma cell lines induced into the lytic cycle by crosslinking cell surface IgG. Electron microscopy revealed the various stages of maturation and egress of progeny virions including mature EBV in irregular cytoplasmic vesicles. Immunofluorescence staining showed that gp350/220, the major EBV glycoprotein, and the viral capsid antigen, p18, efficiently colocalized with a cis-Golgi marker, GM130. gp350/220 partly co-localized with the TGN, which was distributed in a fragmented and dispersed pattern in the cells induced into the lytic cycle. In contrast, limited colocalization was observed between gp350/220 and endosomal markers, such as a multi-vesicular bodies marker, CD63, a recycling endosome marker, Rab11, and a regulatory secretion vesicles marker, Rab27a. Finally, we observed that treatment of cells with brefeldin A, an inhibitor of vesicle trafficking between the endoplasmic reticulum and Golgi apparatus, resulted in the perinuclear accumulation of gp350/220 and inhibition of its distribution to the plasma membrane. Brefeldin A also inhibited the release of infectious EBV. Taken together, our findings support a model in which EBV acquires its final envelope in intracellular compartments containing markers of Golgi apparatus, providing new insights into how EBV matures.